The inFuence of drifting and blowing snow on surface (turbulent) mass- and energy exchange assessed with different methods - Lehning, Michael; Gerber, Franziska; Sigmund, Armin; Brito Melo, Daniela; Huwald, Hendrik; Dujardin, Jérôme; Walter, Benjamin (2022)
Drifting and blowing snow is a dominant process shaping snow-covered surfaces in particular in extreme environments such as high mountains or polar regions. Because the process is complicated to describe, as it covers scales from below 1 mm to several kilometers, it is typically not considered in models or greatly simpli^ed. This impedes our ability to correctly describe the mass- and energy exchange above snow covered surfaces and therefore also to understand the relationship with precipitation patterns. Our contribution addresses this problem by reviewing the current state of understanding. We show based on measurements and large-eddy simulations (LES) that typical bulk Monin–Obukhov formulations for turbulent auxes do not work in the presence of snow transport. More specifically, surface exchange is much more intense than predicted by current large-scale models during snow transport. We further present a new model coupling, CRYOWRF, which introduces the snow model SNOWPACK and a detailed representation of blowing snow to the Weather and Forecasting model (WRF) in order to allow a more accurate representation of surface exchange. We show how this coupled version is able to reproduce observed patterns of blowing snow and its inauence on surface exchange. This includes cases of blowing snow over mountain ridges and large blowing snow clouds from katabatic winds, an hydraulic jump and waves in Antarctica (Figure). Overall, we find that the influence of drifting and blowing snow on surface exchange may have been underestimated in previous (model) assessments and that the highly dynamic exchange associated with drifting and blowing snow has not only implications for the surface mass and energy balance, but potentially also for the isotopic composition of deposited snow.